Evolution of hierarchy of settlements in river-basin scale towards climate change - Yenen, Zekiye; Hamamcioglu, Cenk (INDERSCIENCE ENTERPRISES LTD, 2017)
Fundamental impacts of climate change due to global warming reveal undeniable consequences on planning for future. Taking the question 'have we cognised to incorporate the effects of climate change in planning yet?' into account, this paper brings up the factors of human activities precipitating climate change and its probable impacts on the hierarchy of settlements to the agenda in order to stimulate planners, policy makers, entrepreneurs and other stakeholders to be ready for different possibilities with flexible approaches and efficient adaptation policies. In this context, two main projected scenarios stated by the UNFCCC (2001) and IPCC's (2013) reports are predicted and discussed on the future characteristics of settlement system to undergo a change in the case of Gksu Basin from Turkey. Therefore, reminding river basin (scale) concept as a planning unit to mitigate the impacts of climate change is identified as another useful aim of this paper. Meanwhile, climate change points out the necessity for more and varied, but purpose-focused data to be studied thoroughly by the planners.
Keywords: basin; river basin; basin-based approach; climate change; hierarchy of settlements; Goksu Basin; Mediterranean; Turkey; GROWTH; Environmental Sciences & Ecology